ANALISIS BLACKBOX TESTING DAN USER ACCEPTANCE TESTING TERHADAP SISTEM INFORMASI SOLUSIMEDSOSKU - Wahyudi, Indra; Fahrullah, Fahrullah; Alameka, Faza; Haerullah, Haerullah (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2023)
Websites are very effectively used as information media because there are visual elements in the form of images and text that can impress consumers. Solusimedsosku is a form of e-commerce and an SMM panel platform in Indonesia that provides various social media services. The success and failure of a product development is largely determined by the test results. The testing and implementation that the researchers carried out aims to determine the level of acceptance of the Solusimedsosku website, both in terms of design, service and efficiency so that based on this evidence it can be concluded whether the system being tested has been acceptable or not. The purpose of this study was to find out and analyze the User Acceptance Test Within Information System Solusimedsosku. Based on the results of the analysis, it can be seen that the responses of respondents using the Solusimedsosku information system based on the level of system acceptance taken from 3 aspects of the assessment, namely design (appearance), service, and efficiency are very strong, with a percentage of 84%.